Some integral representations for the Faxén function. Issue 12 (2nd December 2022) - Ansari, Alireza
ABSTRACT: In this paper, we consider the Faxén integral and present some alternative integral representations using the suitable changing of functions in the integrand. These integral representations are derived in terms of the Wright, generalized Wright and Mittag–Leffler functions. An identity is also given for the addition formula of this function.